Minimal invasive intralesional excision of extremity-located osteoid osteomas in children - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
In this retrospective study, we evaluated the efficiency of minimal invasive intralesional extended curettage in the treatment of osteoid osteomas of the extremities in children. Forty-seven children (29 males, 18 females; mean age 10.5 years; range 4-19 years) with osteoid osteoma of the extremities underwent minimal invasive intralesional extended curettage. The exact localization of the nidus was determined preoperatively by thin-section (1-1.5 mm) computed tomography scans, and complete excision of the nidus was performed using a modified burr-down technique. None of the procedures required bone grafting or internal fixation. The median follow-up duration was 59 months (range, 12-136 months). Histopathological confirmation of osteoid osteoma was achieved in all procedures. All patients experienced immediate and complete relief of lesional pain after surgery. Preoperative (a day before surgery) and postoperative (at the time of discharge) mean visual analogue scale scores, questioning the pain derived from osteoid osteoma, were 7.7 +/- 1.2 and 0.3 +/- 0.6, respectively, confirming complete removal of the nidus. Early motion of the involved extremities and mobilization of the patients were achieved within 2 days. The children resumed normal function within 3 weeks. Postoperative complication or recurrence was not encountered in any of the patients. Even though percutaneous radiofrequency thermoablation is accepted as the treatment of choice for extraspinal osteoid osteomas, this technique requires a regional reference institution. Minimal invasive intralesional extended curettage can be performed in conventional institutions, even those not specialized in bone tumor surgery, by orthopedic surgeons with high success and low morbidity rates, in addition to rapid functional recovery. Copyright (C) 2017 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: children; extremity; intralesional excision; osteoid osteoma; PERCUTANEOUS RADIOFREQUENCY COAGULATION; ABLATION; CT; OSTEOBLASTOMA; ADOLESCENTS; BONE